Hexane Economization in Palm Kernel oil Plant: A Study After Process Design Improvement - Sivarao, Subramonian; Nanthakumar, Rajoo; Widodo, W. Sapto; Haeryip , Sihombing (Global Engineers and Technologists Review, 2012)
Hexane (C6H14) is used as a solvent to extract oil from palm kernel to produce crude palm kernel oil (CPKO) which is a common cooking ingredient. The main intention of this research work is to reduce hexane loss during the extraction process of oil from palm kernel. This research project was carried out in a leading vegetable factory in Malaysia. Although this plant managed to get high yield (average 48.5 %) compare with other similar conventional plants in Malaysia but the hexane loss is very high, 8.5 litre/Metric Ton (l/MT) in average. To reduce the hexane loss, few modification jobs were carried out; adding of new shell and tube condenser, sealing of leakages and developed a set of standard operating procedures. Preliminary investigation after the improvement steps found that, reduction of hexane loss showed a decrease of about 30 % from the average of 9.5 % litre/MT of palm kernel 6.5 litre/MT of palm kernel after the improvement. This amounted of hexane savings of 3 litre/MT of palm kernel which is equivalent to about RM 727,660 for 8 months after the process improvement taken into effect.